2017
DOI: 10.1590/0102-33062017abb0083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of El Niño and edge effects on the reproductive phenology and floral visitors of Eschweilera tetrapetala Mori (Lecythidaceae), an endemic species of the Atlantic Forest of northeastern Brazil

Abstract: We compared the reproductive phenology and fl oral visitors of Eschweilera tetrapetala growing along the edge and in the interior of a submontane forest in the Chapada Diamantina mountains, Bahia State, Brazil. We sought to determine if there were inter-annual diff erences in intensity and seasonality associated with environmental conditions, and if there were diff erences in fl oral visitors between the two environmental contexts. Phenological observations were performed for three years, and included the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 55 publications
0
13
1
3
Order By: Relevance
“…(Couto-Santos et al 2015), the latter species is endemic to this unique forest fragment in Bahia State, and threatened with extinction (CNCFlora 2016). Menezes et al (2018) demonstrated that climatic changes (due to ElNiño) and anthropogenic alterations (in this case related to edge creation) influenced the reproductive phenology and floral visitors of E. tetrapetala, whose flowering and fruiting were more intense in the forest interior (and it was visited by potential pollinators only in that context).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Couto-Santos et al 2015), the latter species is endemic to this unique forest fragment in Bahia State, and threatened with extinction (CNCFlora 2016). Menezes et al (2018) demonstrated that climatic changes (due to ElNiño) and anthropogenic alterations (in this case related to edge creation) influenced the reproductive phenology and floral visitors of E. tetrapetala, whose flowering and fruiting were more intense in the forest interior (and it was visited by potential pollinators only in that context).…”
Section: Discussionmentioning
confidence: 99%
“…Phenology, pollination and dispersal modes, especially abiotic syndromes, have been associated with plant strategies that coexist in seasonal contexts and affect ecosystem services (Jara-Gerrero et al 2011;Perez-Harguindeguy et al 2013;Sfair et al 2016). Researchers have reported significant differences in the reproductive phenologies of species as result of the formation of both natural and anthropogenic edges (Cunnigham 2000;Athayde & Morellato 2014;Pires et al 2014;Menezes et al 2018). Edge creation can strongly affect species composition and phenodynamics, strongly influence community functioning and ecosystem processes, as well as decrease the functional diversity of forest patches (Girão et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such a supra-annual flowering also occurs in other igapó tree species, including Aldina latifolia Spruce ex Benth and Cieba pentandra (L.) Gaertn. [74], as well as other members of the genus Eschweilera (e.g., E. tetrapetela S.A. Mori [63]). This form of phenology could allow individual plants to maximize effective energy investment in reproduction, both in terms of attractiveness to pollinators, and as a means of diminishing proportion of (energetically-demanding) produced seed crop lost to seed predators.…”
Section: Discussionmentioning
confidence: 99%
“…They then move in further to reach the nectar, receiving pollen from the fertile anthers of the basal ring in the process [62]. Together, the size and weight of the hood greatly reduce ingress by smaller-bodied nectar and pollen thieves [63]. Members of the Xylocopine genus Xylocopa and the Euglossine genus Eulaema are known pollinators for Eschweilera (e.g., E. decolorans and E. longipes [58]; E. ovata [64]; E. nana [65]).…”
Section: Invertebratesmentioning
confidence: 99%
“…The qualitative method did not generate easily distinguishable intensity peaks. Data collection using the Fournier method, however, has been widely employed in phenological studies due to its efficiency and standardized measurements (Menezes et al, 2018). Quantitative methods require more intensive field efforts, although they proved to be more accurate in demonstrating the intensities of flowering and fruiting as resources invested in pollination and dispersal processes of H. drasticus.…”
mentioning
confidence: 99%